Determinants of capital structure: application to Shariah-compliant firms in Malaysia / Zahariah Sahudin - Sahudin, Zahariah (2017)
This study highlights the sensitivity of capital structure determinants in each sector within the Shariah-compliant firms listed in Bursa Malaysia. Although the proportion of debt financing is similar, each sector adopted different financing patterns. Remarkably, this pattern occurred after the implementation of the Malaysian Capital Market Plan in early 2001. Evolution of the capital market development, particularly the Islamic bonds, or Sukuk, further highlights the vibrancy of the capital market as the main provider of financial resources to the corporate sector. The inconsistencies of results on capital structure in previous literature have been inconclusive but remained the core debatable issue in the finance world. This study is primarily motivated by the issue of the scrutinised determinants still being inconclusive in the area of capital structure. It includes three new variables that are efficiency and bankruptcy risk for firm specific factor and industry concentration for sector specific factor. This is a new contribution to the literature as no work has been done regarding these issues in Shariah-compliant firms in Malaysia. Additionally, it employs two-stage analysis namely the parametric Stochastic Frontier Analysis (SFA) method and the panel data analysis. Employing SFA is to acquire the technical efficiency score of every Shariah-compliant firm. This study quoted revenue efficiency instead of cost efficiency because the firms in the sector are competing to increase the revenue. Additionally, it includes the efficiency as the independent variable to the leverage model. By employing panel data analysis, this study could examine the determinants influencing firm leverage and to analyse relationship of the new variables namely efficiency, bankruptcy risk as well as industry concentration with the firm leverage. Focussing on construction, property, plantation, industrial as well as trade and services sectors for the period of 2002-2011, this study made use of the static models namely Pooled Ordinary Least Square, Fixed Effect and Random Effect Model. Empirical analysis on the determinants reveals that country specific factor (lending rate) and sector specific factor (industry concentration) are significant in influencing the corporate financing decisions, along with firm specific factor (profitability, tangibility and liquidity). Nevertheless, the applicability of capital structure theories such as the trade-off theory, agency theory and pecking order theory diverge across sectors in Malaysia. The pecking order theory and agency theory are found to be the dominant theories governing the corporate financing decision. It indicates strong evidence of hierarchy practised in firms' financing decision. The finding on agency theory being dominant justifies the function of short term debt as a controlling mechanism to mitigate the agency problem, arising within firm across sectors. The firm specific factors (bankruptcy risk, profitability, tangibility, liquidity and firm size) significantly influence the firm leverage in Malaysia. However, the sector specific factor and country specific factor (industry concentration and lending rates) are persistently maintained as the most significant factor to leverage across sectors. Being important, these variables influence the financing decision of the Shariah-compliant firms in Malaysia. As a vital contribution, this study employed the Shariah-compliant firms as samples which have yet to be conducted on determinants of their capital structure and efficiency.